The Role of the Paratrigeminal Nucleus in Vagal Afferent Evoked Respiratory Reflexes: A Neuroanatomical and Functional Study in Guinea Pigs - Driessen, Alexandria K.; Farrell, Michael J.; Mazzone, Stuart B.; McGovern, Alice E. (Frontiers in Physiology, 2015)
The respiratory tree receives sensory innervation from the jugular and nodose vagal sensory ganglia. Neurons of these ganglia are derived from embryologically distinct origins and as such demonstrate differing molecular, neurochemical and physiological phenotypes. Furthermore, whereas nodose afferent neurons project to the nucleus of the solitary tract (nTS), recent neuroanatomical studies in rats suggest that jugular neurons have their central terminations in the paratrigeminal nucleus (Pa5). In the present study we confirm that guinea pigs demonstrate a comparable distinction between the brainstem terminations of nodose and jugular ganglia afferents. Thus, microinjection of fluorescently conjugated cholera toxin B (CT-B) neural tracers into the caudal nTS and Pa5 resulted in highly specific retrograde labelling of neurons in the nodose and jugular ganglia, respectively. Whereas nodose neurons more often expressed 160KD neurofilament proteins and the alpha3 subunit of Na+/K+ ATPase, significantly more jugular neurons expressed the neuropeptides substance P (SP) and, especially, Calcitonin Gene-Related Peptide (CGRP). Indeed, terminal fibers in the Pa5 compared to the nTS were characterized by their significantly greater expression of CGRP, further supporting the notion that jugular afferents project to trigeminal-related brainstem regions. Electrical stimulation of the guinea pig larynx following selective surgical denervation of the nodose afferent innervation to the larynx (leaving intact the jugular innervation) resulted in stimulus dependent respiratory slowing and eventual apnea. This jugular ganglia neuron mediated response was unaffected by bilateral microinjections of the GABAA agonist muscimol into the nTS, but was abolished by muscimol injected into the Pa5. Taken together these data confirm that jugular and nodose vagal ganglia afferent neurons innervate distinct central circuits and support the notion that multiple peripheral and central pathways mediate sensory responses associated with airway irritations.